Sire evaluation considering first lactation yield for improvement of lifetime production in Sahiwal* - Deulkar, P B; Kothekar, M D (The Indian Journal of Animal Sciences, 2012)
Data an 324 Sahiwal cows, progeny of 23 sires maintained at Cattle Breeding farm of Nagpur Veterinary College (NVC) and Agricultural College (AC) farm, Nagpur, were used to evaluate sires for first-lactation yield (LMYâ‚) and lifetime milk production (LTMY). Simple daughter average (D), least squares (LS) and best linear unbiased prediction (BLUP) technique was used to estimate sires breeding value. BLUP technique includes fixed effects of farm, period and season of calving and random effect of sires within farm. Fixed effects in LS method and fixed and random effects in BLUP technique were used to rank sires and to find out correlations among different methods of sire evaluation. The estimates of rank and product moment correlations revealed that correlations of first lactation yield with lifetime production was high and significant (P < 0.01), but not perfect, indicating that all sires would not rank same for first lactation and lifetime production. However, 5 top sires almost had similar rank for both the traits. To improve lifetime productivity of dairy animals, evaluation of top tanked dairy sires for first lactation could be used as future sires. Daughter average method of sire evaluation considering first lactation would improve lifetime productivity. D method was equally good when compared with LS and BLUP method of sire ranking.